JENIS-JENIS TUMBUHAN DI SEKITAR SEKOLAH SMA GKST PALU DAN PENGEMBANGANNYA SEBAGAI MEDIA PEMBELAJARAN - Hariani, Ni Made Mega (JSTT, 2016)
The purpose of this study was to identifying and describing kinds of plant and design as an instructional media in form of booktest about the kinds of plants at SMA GKST Palu. This was a survey research using descriptive method with cruising technique and continued by the research development. The kind of indicator was focussed on the morphological characteristics organs, habitat of plants. The indicator of observation for the feasibility learning media were: contents, design and media. The analysis technique obtained descriptively and for qualitative learning media. The result show that 74 kinds of plants classified into 44 family and 68 genus. The results of the development in this case the pocket book obtained from the validation of content expert, design expert and media expert with the percentage 91.00 percent, 95.90 percent and 97.50 percent, a peer assesment or biology teacher was 89.23 percent, small group assesment was 95.11 percent and large group assesment was 98.67 percent. The percentage value when converting into the eligibility criteria in the category of decent. It can be concluded that the percentage value can be categorized into feasible category and can be used as biology learning media.